Impact of Weed Management Practices on Biomass and Grain Yield of Two Varieties of Paddy in Lowland Area of Far-Western Nepal - Bhatt, M. D.; Pant, S. R.; Singh, S. P. (Nepal Journal of Science and Technology, 2010)
Experiments were conducted in two varieties of transplanted paddy (cv. Radha-4 and Neemai) during the rainy season of 2004-2005 in the Far-Western Terai region of Nepal to assess the effect of weed management practice. Four experiments were conducted in randomized block design with three replications viz. unweeded (T0), weed free (TT), manured plus twice hand-weeded after 25 and 50 days of transplanting (T1), and chemical fertilizer plus butachlor (weedicide) application (1.5 kg ha-1) (T2). A total of 48 weed species were identified with densities of 208 ind. m-2 in Radha-4 and 196 ind. m-2 in Neemai. The mean maximum biomass of paddy in weed-free plots were 3553.6 and 3588.4 g m-2 in Radha-4 and Neemai respectively. This biomass was more or less similar to twice hand-weeded plots and herbicide treated plots being 1.3% lowering in both the varieties, compared to weed-free plots. Compared to weed-free plots, the biomass reduction in unweeded plots was recorded 26.1% lower in Radha-4 and 26.3% in Neemai. The weed biomass was recorded highest in unweeded plots (296.9 and 236.2 g m-2) and lowest 155.7 and 109.1 g m-2 in twice hand-weeded plots. The trend of grain yield in both the varieties were: weed free (TT) > manured plus twice hand-weeded after 25 and 50 days of transplanting (T1) > chemical fertilizer plus butachlor application (1.5 kg/ha) (T2) > unweeded (T0). Key words: Rice; Weeds control; Western Terai; Biomass DOI: 10.3126/njst.v9i0.3157 Nepal Journal of Science and Technology 9 (2008) 15-20